Horizontal together : art, dance, and queer embodiment in 1960s New York - Aramphongphan, Paisid (Rethinking art's histories., 2021)
Horizontal together is an up-close look at the cultural and political power of the langourous queer body, combining historical research, queer theory and the analysis of bodily gestures. The book presents a dancerly story of 1960s art focusing on Andy Warhol, underground filmmaker Jack Smith and experimental dance star Fred Herko.